Volume 2D: Turbomachinery 2017
DOI: 10.1115/gt2017-63202
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a Turbofan Engine With Ice Crystal Ingestion in the NASA Propulsion System Laboratory

Abstract: The main focus of this study is to apply a computational tool for the flow analysis of the turbine engine that has been tested with ice crystal ingestion in the Propulsion Systems Laboratory (PSL) at NASA Glenn Research Center. The PSL has been used to test a highly instrumented Honeywell ALF502R-5 (LF11) turbofan engine at simulated altitude operating conditions. Test data analysis with an engine cycle code and a compressor flow code was conducted to determine the values of key icing parameters that can indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The basis of this criteria is described in Ref. [8]. By finding regions of icing, parameter sweeps were conducted to move the location of accretion and change the accretion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The basis of this criteria is described in Ref. [8]. By finding regions of icing, parameter sweeps were conducted to move the location of accretion and change the accretion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that air temperatures above freezing can be conducive to ice crystal accretion. This has been observed both in tunnel tests [9], [10] and in engine data analysis [1], [39]. However, models and data for particle sticking in these warm conditionswhether empirical or analyticalare generally scarce.…”
Section: Sticking On Surfaces Abovementioning
confidence: 88%
“…Instrumentation development to acquire details on the cloud generation in the facility and the ability to fully instrument an engine allows researchers better understand of the underlying physical mechanisms in order to further improve and validate the existing in-house engine ice accretion simulation and icing risk prediction codes. Those early research works formed the basis of the icing risk criteria used in the development of the NASA in-house 1D Icing Risk tool [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%